Biomechanical Regulatory Factors and Therapeutic Targets in Keloid Fibrosis - Feng, Fan; Liu, Mingying; Pan, Lianhong; Wu, Jiaqin; Wang, Chunli; Yang, Li; Liu, Wanqian; Xu, Wei; Lei, Mingxing (Frontiers in Pharmacology, 2022)
Keloids are fibroproliferative skin disorder caused by abnormal healing of injured or irritated skin and are characterized by excessive extracellular matrix (ECM) synthesis and deposition, which results in excessive collagen disorders and calcinosis, increasing the remodeling and stiffness of keloid matrix. The pathogenesis of keloid is very complex, and may include changes in cell function, genetics, inflammation, and other factors. In this review, we aim to discuss the role of biomechanical factors in keloid formation. Mechanical stimulation can lead to excessive proliferation of wound fibroblasts, deposition of ECM, secretion of more pro-fibrosis factors, and continuous increase of keloid matrix stiffness. Matrix mechanics resulting from increased matrix stiffness further activates the fibrotic phenotype of keloid fibroblasts, thus forming a loop that continuously invades the surrounding normal tissue. In this process, mechanical force is one of the initial factors of keloid formation, and matrix mechanics leads to further keloid development. Next, we summarized the mechanotransduction pathways involved in the formation of keloids, such as TGF-β/Smad signaling pathway, integrin signaling pathway, YAP/TAZ signaling pathway, and calcium ion pathway. Finally, some potential biomechanics-based therapeutic concepts and strategies are described in detail. Taken together, these findings underscore the importance of biomechanical factors in the formation and progression of keloids and highlight their regulatory value. These findings may help facilitate the development of pharmacological interventions that can ultimately prevent and reduce keloid formation and progression.